The Effect of Video Recording on Students’ Speaking Skill at Tenth Grade Students of SMAN 7 Kota Tangerang Academic Year 2018/2019 - Haoro, Umayatul; Ramalia, Tenia (Foremost Journal, 2020)
Abstract This study had quasi-experimental design which was intended to get empirical evidence of the effectiveness of using video recorded speaking on students' speaking skill. The population was the tenth grade students of SMAN 7 Kota Tangerang. The sample was 68 students chosen through classified into two classes, experimental and controlled class. The instrument was test where students must practice dialogue. The results of testing normality from video recording (experimental) in Kolmogorov-Smirnov test and the Shapiro-Wilk test is not normally but in the learning outcomes from using traditional method (control) with Kolmogorov-Smirnov test is normally distributed and the Shapiro-Wilk test is not normally distributed. The next analysis homogeneity test the result that the significance value > 0.05 (0.147 > 0.05), thus it can be concluded that the variants of both data groups, control and experimental classes are homogenous. The last based on the results of the Non parametric tests the data presented in table 4.5 indicate that p > 0.01, meaning that there is a difference between experiment class and control class in terms of learning outcomes of Speaking Skill students. It can be said that the level of students' speaking skill between experiment class and control class is basically different. Thus, Ho is rejected and Ha is accepted. It means there is a significant effect of video recording on students'speaking skill. Keyword: correlative conjunction, speaking, video recorded speaking.